Treatment of Wastewater Using Reverse Osmosis for Irrigation Purposes - Hafiz, MhdAmmar; Hawari, Alaa H.; Alfahel, Radwan (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This work investigates the performance of reverse osmosis (RO) for the reclamation of treated sewage effluent (TSE) to be used as irrigation water for food crops. The feed water used in this study was a real sample of ultra-filtered tertiary treated sewage effluent (TSE). Reverse osmosis (RO) was evaluated using the following experimental conditions applied pressure (10 - 20) bar, flow rate 3.5 LPM and (BW30LE) membrane. The performance of RO was evaluated according to the water flux and rejection of dissolved solids. The final water quality was compared with irrigation water standards. The results reported in this study show that reverse osmosis (RO) is capable of reclaiming treated sewage effluent (TSE) to be used as irrigation water for food crops. The maximum average flux was 77.7 LMH achieved using a feed pressure of 16 bar. The permeate water generated using RO had high quality which met the irrigation standards for food crops.